Strategi manajemen keuangan UMKM dalam meningkatkan akses pembiayaan dan keberlanjutan ekonomi di Indonesia: Sebuah Narrative Literature Review - Nurul Habiburrahmah; Raden Roro Yulianti Prihatiningrum (JURNAL BISNIS DAN PEMBANGUNAN, 2026)
This research aims to test the influence of e-Satisfaction, e-Service Quality, e-trust on e-loyalty customer Marketplace Shopee. The approach used in this research is quantitative, with a casual associative research type. The sampling method used nonprobability sampling with the purposive sampling method for 384 users of the Shopee marketplace application. Data collection uses a Google Form questionnaire which is shared via Whatsapp, Instagram and Facebook. Data analysis using SmartPLS 4.0 software. The research results show that e-service quality influences the e-satisfaction of users of the Shopee Marketplace application, e-service quality influences the e-trust of users of the Shopee Marketplace application, e-service quality influences the of e-loyalty Customers of users of the Shopee Marketplace application, , e- Satisfaction has no effect on e-Trust, e-satisfaction has no effect on e-loyalty Customers who use the Shopee Marketplace application, e-trust has no effect on e-loyalty Customers who use the Shopee Marketplace application